Language choice and language shift in the tri generational Hubei families in Malaysia / Low Mai Yen - Low , Mai Yen (2019)
Different Chinese varieties were used among the different linguistic groups for cultural identity and kinship ties (Sim, 2012) during the Chinese diaspora in South East Asia in the early 1900’s. Thus, the initial Hubei migrants to Malaya spoke the Tianmen/Hubei dialect for cultural identity. However, multilingualism in the society has impacted the language choice and language maintenance of the heritage language in the Hubei families in Malaysia. Data obtained from forty-five respondents based on a questionnaire adapted from Coluzzi, Riget & Wang (2013) and an interview indicated a shift in the use of the mother tongue to other languages in the home, social and socio-cultural domains. Lamentably, there is a loss of inter-generational transmission of the language as the Hubei community in Malaysia is progressively losing members of the older generation who are the authentic native speakers of the heritage language.